A Novel Downlink IM-NOMA Scheme - Abdullateef Almohamad (16870074) (2021)
In the next generations of communication systems, resources' scarcity devolves to a more critical point as a consequence of the expected massive number of users to be served. Furthermore, the users' contradicting requirements on quality of service forces the network to behave in a dynamic way in terms of the multiple access orchestration and resource assignment between users. Hence, the linear relation between the number of served users and the required (orthogonal or semi-orthogonal) resources in the orthogonal multiple access (OMA) schemes is no longer sufficient. As promising candidates, Non-orthogonal multiple access (NOMA) schemes and index modulation (IM) techniques are emerging to satisfy the ever-increasing connectivity demands and spectral efficiency. In this article, a novel IM-based NOMA downlink scheme, termed as IM-NOMA, is proposed, where the base station (BS) selects a channel or more to serve each user based on the IM concept and the corresponding power level is allocated based on the NOMA concept. At the users' ends, maximum likelihood and successive interference cancellation (SIC) detection methods are considered and their error rate, outage probability and computational complexity are studied. Simulation results confirm the advantage of the proposed IM-NOMA scheme and that it can outperform the conventional NOMA system. Other Information Published in: IEEE Open Journal of the Communications Society License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/ojcoms.2021.3051082